Expanding the farmer's share of the food dollar: exploring the potential effects of emerging food supply chain models - Thilmany-McFadden, Dawn, author; Bauman, Allie, author; Jablonski, Becca B. R., author; Angelo, Blake, author; Shideler, Dave, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2015)
In response to growing public interest in regionally focused food systems, a proliferation of business models for expanding sales into these markets is occurring. Given that some of the growth in regional food systems is anchored in the idea of increasing the share of the food dollar retained by farmers, if not their allied business associates and communities, it is important to understand how different models address those goals.
July 2015.
Keywords: supply chains; market autonomy; sales; markets